High Fidelity Simulation: A Tool to achieve significant learning in undergraduate medical students of a private university - Mas-Ubillús, Guiliana (2023)
High fidelity simulation has emerged as an important technological method for learning and teaching in complex clinical scenarios of specialized areas, enabling to develop both technical and non-technical skills. The experience described is related to the curricular insertion of high fidelity simulation in fourth and fifth grade of undergraduate medical students (2018-2019) of the Faculty of Medicine Universidad Peruana Cayetano Heredia (UPCH) with the objective to establish diagnoses, request and interpret auxiliary tests, establish and evaluate the response to an initial treatment and establish effective communication with other health professionals, through the use of clinical scenarios with highly complex simulators, emphasizing debriefing with immediate good judgment, providing insights into the learning objectives of each case and concluding the sessions with the learning experiences of each student.